Method for improving performance of crushed Fe-Si-Al and Fe-Si-Al

The performance of crushed ferrosilicon aluminum is improved through ball milling and annealing, and the problems of high losses and low DC bias performance are solved, and the low cost and efficient preparation of ferrosilicon aluminum magnetic powder core is achieved, which is suitable for large-scale promotion.

CN119187575APending Publication Date: 2024-12-27HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411322624.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, crushed ferrosilicon aluminum has high losses and low DC bias performance, high cost and complex process, making it difficult to promote and use on a large scale.

Method used

By ball-milling the broken ferrosilicon aluminum, annealing in a protective atmosphere, adding glue and pressing, ferrosilicon aluminum with low loss and high DC biasing properties were prepared.

Benefits of technology

The loss at 100kHz/100mT is not higher than 550mW/cm3, and the DC bias performance under the 100Oe magnetic field strength is not less than 27%, and the cost is low and the process is simple, making it suitable for large-scale promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005054429520000141
    Figure BDA0005054429520000141
  • Figure BDA0005054429520000151
    Figure BDA0005054429520000151
  • Figure BDA0005054429520000161
    Figure BDA0005054429520000161
Patent Text Reader

Abstract

The invention provides a method for improving the performance of broken Fe-Si-Al and Fe-Si-Al, and the method comprises the following steps: carrying out ball milling on the broken Fe-Si-Al, adding an acid solution in the ball milling process, carrying out first annealing in a protective atmosphere to obtain Fe-Si-Al powder, mixing the obtained Fe-Si-Al powder with glue, and pressing to obtain the Fe-Si-Al powder. And carrying out second annealing in a protective atmosphere to obtain the Fe-Si-Al. According to the method for improving the performance of the broken Fe-Si-Al, Fe-Si-Al with low loss and high direct-current bias performance can be prepared, the loss of the prepared Fe-Si-Al is not higher than 550 mW / cm < 3 > under 100 kHz / 100 mT, and the direct-current bias performance is not lower than 27% under the magnetic field intensity of 100 Oe; meanwhile, the method has the advantages of being low in cost, simple in process and easy to popularize and use on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic material preparation, and relates to a method for improving the performance of crushing iron-silicon-aluminum, and in particular to a method for improving the performance of crushing iron-silicon-aluminum and the iron-silicon-aluminum. Background Art

[0002] With the rapid development of the electronic technology industry, the miniaturization, low loss and high superposition of devices have become an inevitable trend of development, and Sendust magnetic powder cores have the advantages of low loss and high DC bias performance, and will be widely used. However, although the performance of Sendust produced by the gas atomization method is better, the cost is too high; while the production method of crushed Sendust is simple, the yield is high and the cost is low, but its shape is irregular particles, there are more sharp corners, and the fluidity is poor. Compared with the Sendust produced by the gas atomization method, it has high loss and low DC bias performance, so a production method is needed to improve the performance of crushed Sendust.

[0003] CN107919202A discloses a method for preparing a high DC bias and high frequency stability sendust aluminum powder core. The method comprises the following steps: selecting crushed sendust aluminum powder with a particle size distribution of -100 mesh to +325 mesh; adding 0.3% to 1.5% epoxy resin, 0.2% to 0.5% SiO2 powder, 1.0% acetone and 9.0% water in a mass ratio based on the mass of the crushed sendust aluminum powder; heating to 100°C to 150°C after stirring at room temperature, and continuing to keep warm and stir for 10 minutes to 30 minutes; and sieving the insulating coating powder using a 100-mesh screen.

[0004] CN107610872A discloses a method for preparing a composite powder core with a magnetic permeability of 60 for high-power reactors. The composite magnetic powder is prepared by selecting 40.0% to 50.0% iron silicon powder and 50.0% to 60.0% crushed iron silicon aluminum powder by mass, and phosphoric acid and CaO powder are used to insulate and coat the magnetic powder particles to prepare a composite soft magnetic powder core with an effective magnetic permeability of 60. The composite soft magnetic powder core prepared by the invention has excellent DC bias performance, and the powder core loss is less than 500mW / cm under the conditions of frequency 50kHz and 100mT. 3 .

[0005] The currently disclosed methods for improving the performance of crushing iron-silicon-aluminum have certain defects, such as limited reduction of loss and improvement of DC bias performance, high cost and complicated process, which are not conducive to large-scale promotion and use. Therefore, it is very important to develop and design a new method for improving the performance of crushing iron-silicon-aluminum and iron-silicon-aluminum. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a method for improving the performance of crushing sendust and a sendust magnetic powder core. The method for improving the performance of crushing sendust provided by the present invention can prepare sendust with low loss and high DC bias performance. The loss of the prepared sendust at 100kHz / 100mT is not higher than 550mW / cm 3 , the DC bias performance under a magnetic field strength of 100Oe is not less than 27%; at the same time, the method also has the advantages of low cost, simple process and easy large-scale promotion and use.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for improving the performance of crushing iron, silicon and aluminum, the method comprising:

[0009] The crushed sendust is ball-milled, an acid solution is added during the ball-milling process, and then a first annealing is performed in a protective atmosphere to obtain sendust powder, the obtained sendust powder is mixed with glue and then pressed, and then a second annealing is performed in a protective atmosphere to obtain sendust.

[0010] The method for improving the crushing performance of sendust provided by the present invention can prepare sendust with low loss and high DC bias performance, and the loss of the prepared sendust at 100kHz / 100mT is not higher than 550mW / cm 3 , the DC bias performance under a magnetic field strength of 100Oe is not less than 27%; at the same time, the method also has the advantages of low cost, simple process and easy large-scale promotion and use.

[0011] Preferably, the ball mill uses first grinding balls and second grinding balls with different diameters.

[0012] Preferably, the size of the first grinding ball is 2-4 mm, and the size of the second grinding ball is 4-6 mm.

[0013] The size of the first grinding ball of the present invention is 2-4 mm, for example, it can be 2 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm, 3 mm, 3.2 mm, 3.4 mm, 3.6 mm, 3.8 mm or 4 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] The size of the second grinding ball in the present invention is 4 to 6 mm, for example, it can be 4 mm, 4.2 mm, 4.4 mm, 4.6 mm, 4.8 mm, 5 mm, 5.2 mm, 5.4 mm, 5.6 mm, 5.8 mm or 6 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the mass ratio of the first grinding ball to the second grinding ball is (2-4):1, for example, it can be 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the mass ratio of all grinding balls in the ball mill to the mass ratio of the crushed iron, silicon and aluminum is (4-8):1, for example, it can be 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1 or 8:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the ball milling time is 8 to 12 h, for example, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h or 12 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the rotation speed of the ball mill is 50-100 r / min, for example, it can be 50 r / min, 55 r / min, 60 r / min, 65 r / min, 70 r / min, 75 r / min, 80 r / min, 85 r / min, 90 r / min, 95 r / min or 100 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the mass ratio of the crushed iron silicon aluminum to the added acid solution during the ball milling process is 1:(1-2), for example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the acid solution comprises any one of nitric acid solution, sulfuric acid solution or hydrochloric acid solution or a combination of at least two thereof, typical but non-limiting combinations include a combination of nitric acid solution and sulfuric acid solution, a combination of sulfuric acid solution and hydrochloric acid solution, or a combination of nitric acid solution, sulfuric acid solution and hydrochloric acid solution, preferably a nitric acid solution.

[0021] Preferably, the volume concentration of the acid solution is 0.5-1.5%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the process of washing, drying and screening is carried out in sequence between the ball milling and the first annealing.

[0023] Preferably, the cleaning solution used for cleaning includes ethanol.

[0024] Preferably, the first annealing includes a first heating and a first heat preservation performed sequentially.

[0025] Preferably, the first heating rate is 2-3°C / min, and the end point temperature is 620-630°C.

[0026] The first heating rate of the present invention is 2 to 3°C / min, for example, it can be 2°C / min, 2.1°C / min, 2.2°C / min, 2.3°C / min, 2.4°C / min, 2.5°C / min, 2.6°C / min, 2.7°C / min, 2.8°C / min, 2.9°C / min or 3°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] The end temperature of the first heating in the present invention is 620-630°C, for example, it can be 620°C, 621°C, 622°C, 623°C, 624°C, 625°C, 626°C, 627°C, 628°C, 629°C or 630°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the first insulation time is 60 to 120 min, for example, it can be 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, 100 min, 105 min, 110 min, 115 min or 120 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the mixing includes: first mixing the coupling agent solution with the obtained sendust powder, stirring until the solvent of the coupling agent solution is completely volatilized to obtain a first mixed material; second mixing glue with a glue solvent to obtain a glue solution; and third mixing the obtained first mixed material with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized.

[0030] Preferably, the mass ratio of the coupling agent to the sendust powder in the coupling agent solution is (1-3):100, for example, it can be 1:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100, 2:100, 2.2:100, 2.4:100, 2.6:100, 2.8:100 or 3:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the coupling agent comprises a silane coupling agent.

[0032] Preferably, the concentration of the coupling agent in the coupling agent solution is 95-99.9%, for example, 95%, 96%, 97%, 98%, 99% or 99.9%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the solvent of the coupling agent solution includes ethanol and / or acetone.

[0034] In the present invention, glue is used to achieve bonding of the first mixed material.

[0035] Preferably, the mass ratio of the glue to the sendust powder obtained in step (2) is (1-3):100, for example, it can be 1:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100, 2:100, 2.2:100, 2.4:100, 2.6:100, 2.8:100 or 3:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0036] Preferably, the glue solvent comprises acetone and / or ethanol.

[0037] Preferably, the pressing comprises ring pressing to obtain a ring embryo body.

[0038] Preferably, the pressure of the ring pressing treatment is 1800-2000 MPa, for example, it can be 1800 MPa, 1820 MPa, 1840 MPa, 1860 MPa, 1880 MPa, 1900 MPa, 1920 MPa, 1940 MPa, 1960 MPa, 1980 MPa or 2000 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the second annealing includes a second heating step and a second heat preservation step performed sequentially.

[0040] Preferably, the second heating rate is 2-4°C / min, and the end temperature is 650-750°C.

[0041] The second heating rate of the present invention is 2 to 4°C / min, for example, it can be 2°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min or 4°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] The terminal temperature of the second heating process of the present invention is 650-750°C, for example, it can be 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the second insulation time is 30 to 90 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min or 90 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] As a preferred technical solution of the method of the present invention, the method comprises:

[0045] (1) ball milling the crushed iron-silicon-aluminum at a speed of 50 to 100 r / min for 8 to 12 hours, and then washing, drying and sieving in sequence to obtain a ball-milled material;

[0046] The ball mill uses a first grinding ball with a diameter of 2 to 4 mm and a second grinding ball with a diameter of 4 to 6 mm, the mass ratio of the first grinding ball to the second grinding ball is (2 to 4):1, the mass ratio of all grinding balls to the crushed iron-silicon-aluminum is (4 to 8):1, and an acid solution with a volume concentration of 0.5 to 1.5% is added during the ball milling process, and the mass ratio of the crushed iron-silicon-aluminum to the added acid solution is 1:(1 to 2);

[0047] (2) heating the ball-milled material obtained in step (1) to 620-630° C. at a rate of 2-3° C. / min in a protective atmosphere and then keeping the temperature for 60-120 min to obtain sendust powder;

[0048] (3) first mixing the coupling agent solution with the sendust powder obtained in step (2), stirring until the solvent of the coupling agent solution is completely volatilized, to obtain a first mixed material; second mixing glue with the glue solvent to obtain a glue solution; third mixing the first mixed material with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized, and then performing a ring pressing treatment at a pressure of 1800 to 2000 MPa to obtain a ring embryo;

[0049] The concentration of the coupling agent in the coupling agent solution is 97%, and the mass ratio of the coupling agent in the coupling agent solution to the sendust powder obtained in step (2) is 2:100; the mass ratio of the glue to the sendust powder obtained in step (2) is 2:100;

[0050] (4) The ring body obtained in step (3) is heated to 650-750° C. at a rate of 2-4° C. / min in a protective atmosphere and then kept at this temperature for 30-90 min to obtain Sendust.

[0051] In a third aspect, the present invention provides Sendust, which is obtained by the method described in the first aspect.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] The method for improving the crushing performance of sendust provided by the present invention can prepare sendust with low loss and high DC bias performance, and the loss of the prepared sendust at 100kHz / 100mT is not higher than 550mW / cm 3 , the DC bias performance under a magnetic field strength of 100Oe is not less than 27%; at the same time, the method also has the advantages of low cost, simple process and easy large-scale promotion and use. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum, the method comprising:

[0057] (1) ball milling the crushed iron-silicon-aluminum at a speed of 75 r / min for 10 h, and then washing, drying and sieving in sequence to obtain a ball-milled material;

[0058] The ball mill uses a first grinding ball with a diameter of 3 mm and a second grinding ball with a diameter of 5 mm, the mass ratio of the first grinding ball to the second grinding ball is 3:1, the mass ratio of all the grinding balls to the crushed sendustrine is 6:1, and a nitric acid solution with a volume concentration of 1% is added during the ball milling process, and the mass ratio of the crushed sendustrine to the added nitric acid solution is 1:1;

[0059] (2) heating the ball-milled material obtained in step (1) to 625° C. at a rate of 2.5° C. / min in a nitrogen atmosphere and then keeping the temperature for 90 min to obtain sendust powder;

[0060] (3) first mixing the ethanol solution of the coupling agent with the sendust powder obtained in step (2), stirring until the ethanol in the ethanol solution of the coupling agent is completely volatilized, to obtain a first mixed material; second mixing glue and acetone to obtain an acetone solution of glue; thirdly mixing the first mixed material obtained with the acetone solution of the glue obtained, stirring until the acetone in the acetone solution of the glue is completely volatilized, and then performing a ring pressing process at a pressure of 1900 MPa to obtain a ring embryo;

[0061] The concentration of the coupling agent in the coupling agent solution is 97%, and the mass ratio of the coupling agent in the coupling agent solution to the sendust powder obtained in step (2) is 2:100; the mass ratio of the glue to the sendust powder obtained in step (2) is 2:100;

[0062] (4) The ring embryo obtained in step (3) is heated to 700° C. at a rate of 3° C. / min in a nitrogen atmosphere and then kept at this temperature for 60 min to obtain sendust.

[0063] Example 2

[0064] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum, the method comprising:

[0065] (1) ball milling the crushed iron-silicon-aluminum at a speed of 50 r / min for 12 h, and then washing, drying and sieving in sequence to obtain a ball-milled material;

[0066] The ball mill uses a first grinding ball with a diameter of 2 mm and a second grinding ball with a diameter of 6 mm, the mass ratio of the first grinding ball to the second grinding ball is 2:1, the mass ratio of all the grinding balls to the crushed sendustrine is 4:1, and an acid solution with a volume concentration of 1.5% is added during the ball milling process, and the mass ratio of the crushed sendustrine to the added acid solution is 1:1;

[0067] (2) heating the ball-milled material obtained in step (1) to 620° C. at a rate of 2° C. / min in a protective atmosphere and then keeping the temperature for 120 min to obtain sendust powder;

[0068] (3) first mixing the coupling agent solution with the sendust powder obtained in step (2), stirring until the solvent of the coupling agent solution is completely volatilized, to obtain a first mixed material; second mixing glue with the glue solvent to obtain a glue solution; third mixing the first mixed material obtained with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized, and then performing a ring pressing treatment at a pressure of 1800 MPa to obtain a ring embryo;

[0069] The concentration of the coupling agent in the coupling agent solution is 99.9%, and the mass ratio of the coupling agent in the coupling agent solution to the sendust powder obtained in step (2) is 3:100; the mass ratio of the glue to the sendust powder obtained in step (2) is 1:100;

[0070] (4) The ring embryo obtained in step (3) is heated to 750° C. at a rate of 4° C. / min in a protective atmosphere and then kept at this temperature for 30 min to obtain sendust.

[0071] Example 3

[0072] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum, the method comprising:

[0073] (1) ball milling the crushed iron-silicon-aluminum at a speed of 100 r / min for 8 h, and then washing, drying and sieving in sequence to obtain a ball-milled material;

[0074] The ball mill uses a first grinding ball with a diameter of mm and a second grinding ball with a diameter of 4 mm, the mass ratio of the first grinding ball to the second grinding ball is 4:1, the mass ratio of all the grinding balls to the crushed sendustrine is 8:1, and an acid solution with a volume concentration of 0.5% is added during the ball milling process, and the mass ratio of the crushed sendustrine to the added acid solution is 1:2;

[0075] (2) heating the ball-milled material obtained in step (1) to 630° C. at a rate of 3° C. / min in a protective atmosphere and then keeping the temperature for 60 min to obtain sendust powder;

[0076] (3) first mixing the coupling agent solution with the sendust powder obtained in step (2), stirring until the solvent of the coupling agent solution is completely volatilized, to obtain a first mixed material; second mixing glue with a glue solvent to obtain a glue solution; third mixing the first mixed material obtained with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized, and then performing a ring pressing treatment at a pressure of 2000 MPa to obtain a ring embryo;

[0077] The concentration of the coupling agent in the coupling agent solution is 95%, and the mass ratio of the coupling agent in the coupling agent solution to the sendust powder obtained in step (2) is 1:100; the mass ratio of the glue to the sendust powder obtained in step (2) is 3:100;

[0078] (4) The ring body obtained in step (3) is heated to 650° C. at a rate of 2° C. / min in a protective atmosphere and then kept at this temperature for 90 min to obtain sendust.

[0079] Example 4

[0080] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the concentration of the nitric acid solution in step (1) is 0.5%, the rest is the same as that of embodiment 1.

[0081] Example 5

[0082] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the concentration of the nitric acid solution in step (1) is 1.5%, the rest is the same as that of embodiment 1.

[0083] Example 6

[0084] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of crushed iron-silicon-aluminum to the added nitric acid solution in step (1) is 1:1, the rest is the same as that in embodiment 1.

[0085] Example 7

[0086] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of crushed iron-silicon-aluminum to the added nitric acid solution in step (1) is 1:2, the rest is the same as that in embodiment 1.

[0087] Example 8

[0088] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of all grinding balls to the crushed iron-silicon-aluminum in step (1) is 4:1, the rest is the same as that in embodiment 1.

[0089] Example 9

[0090] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of all grinding balls to the crushed iron-silicon-aluminum in step (1) is 8:1, the rest is the same as that in embodiment 1.

[0091] Example 10

[0092] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling for 8 hours in step (1), the rest is the same as that of embodiment 1.

[0093] Embodiment 11

[0094] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the 12h ball milling in step (1), the rest is the same as that in embodiment 1.

[0095] Example 12

[0096] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling at a rotation speed of 50 r / min in step (1), the rest is the same as that of embodiment 1.

[0097] Embodiment 13

[0098] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling at a rotation speed of 100 r / min in step (1), the rest is the same as that of embodiment 1.

[0099] Embodiment 14

[0100] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the final temperature of the heating in step (2) is 620°C, that is, the insulation temperature is 620°C, the rest is the same as that of embodiment 1.

[0101] Embodiment 15

[0102] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the final temperature of the heating in step (2) is 630°C, that is, the insulation temperature is 630°C, the rest is the same as that of embodiment 1.

[0103] Example 16

[0104] This embodiment provides a method for improving the performance of crushing sendustine, which is the same as that of embodiment 1 except that the mass ratio of the glue in step (3) to the sendustine powder obtained in step (2) is 1:100.

[0105] Embodiment 17

[0106] This embodiment provides a method for improving the crushing performance of sendustine, except that the mass ratio of the glue in step (3) to the sendustine powder obtained in step (2) is 3:100, the rest is the same as that of embodiment 1.

[0107] Embodiment 18

[0108] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the concentration of the nitric acid solution in step (1) is 0.3%, the rest is the same as that of embodiment 1.

[0109] Embodiment 19

[0110] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the concentration of the nitric acid solution in step (1) is 2%, the rest is the same as that of embodiment 1.

[0111] Embodiment 20

[0112] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of crushed iron-silicon-aluminum to the added nitric acid solution in step (1) is 2:1, the rest is the same as that in embodiment 1.

[0113] Embodiment 21

[0114] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum, except that the mass ratio of crushed iron-silicon-aluminum to the added nitric acid solution in step (1) is 1:3, and the rest is the same as that in embodiment 1.

[0115] Embodiment 22

[0116] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of all grinding balls to the crushed iron-silicon-aluminum in step (1) is 2:1, the rest is the same as that in embodiment 1.

[0117] Embodiment 23

[0118] This embodiment provides a method for improving the performance of crushing iron-silicon-aluminum. Except that the mass ratio of all grinding balls to the crushed iron-silicon-aluminum in step (1) is 10:1, the rest is the same as that in embodiment 1.

[0119] Embodiment 24

[0120] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling for 6 hours in step (1), the rest is the same as that in embodiment 1.

[0121] Embodiment 25

[0122] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the 14h ball milling in step (1), the rest is the same as that in embodiment 1.

[0123] Embodiment 26

[0124] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling at a rotation speed of 40 r / min in step (1), the rest is the same as that of embodiment 1.

[0125] Embodiment 27

[0126] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except for the ball milling at a rotation speed of 110 r / min in step (1), the rest is the same as that of embodiment 1.

[0127] Embodiment 28

[0128] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the terminal temperature of the heating in step (2) is 615°C, that is, the insulation temperature is 615°C, the rest is the same as that of embodiment 1.

[0129] Embodiment 29

[0130] This embodiment provides a method for improving the performance of crushing iron, silicon and aluminum. Except that the terminal temperature of the heating in step (2) is 635°C, that is, the insulation temperature is 635°C, the rest is the same as that of embodiment 1.

[0131] Embodiment 30

[0132] This embodiment provides a method for improving the crushing performance of sendustine, except that the mass ratio of the glue in step (3) to the sendustine powder obtained in step (2) is 0.5:100, the rest is the same as that of embodiment 1.

[0133] Embodiment 31

[0134] This embodiment provides a method for improving the crushing performance of sendustine, which is the same as that of embodiment 1 except that the mass ratio of the glue in step (3) to the sendustine powder obtained in step (2) is 4:100.

[0135] Comparative Example 1

[0136] This comparative example provides a method for improving the performance of crushing iron, silicon and aluminum. Except for omitting the addition of nitric acid solution during the ball milling process in step (1), the rest is the same as Example 1.

[0137] Comparative Example 2

[0138] This comparative example provides a method for improving the performance of crushing iron, silicon and aluminum. Except for omitting step (2), that is, directly mixing the ball-milled material obtained in step (1) with the coupling agent solution for the first time, the rest is the same as Example 1.

[0139] Comparative Example 3

[0140] This comparative example provides a crushed sendustine.

[0141] The sendust obtained by the method for improving the performance of crushed sendust in Examples 1 to 31 and Comparative Examples 1 and 2, and the crushed sendust provided in Comparative Example 3 were subjected to median particle size test, density test, relative magnetic permeability test, loss test and 100 Oe DC bias performance test;

[0142] The method for testing the median particle size is as follows: using a laser particle size tester for testing, and the test results are shown in Table 1;

[0143] The method of density test is: measure its weight and size, and obtain density by calculation. The test results are shown in Table 1;

[0144] The loss test method is: using the Japanese Iwasaki BH analyzer SY-8218, the loss at 100kHz / 100mT is shown in Table 1;

[0145] The DC bias performance test method is: using the DC superposition method to test, and the DC bias performance under 100Oe is shown in Table 1.

[0146] Table 1

[0147]

[0148]

[0149]

[0150] From Table 1, we can get:

[0151] (1) The sendust obtained by the method for improving the crushing performance of sendust in Examples 1 to 17 has a smaller median particle size, a higher density, a lower magnetic loss at 100kHz / 100mT, and a higher 100Oe DC bias performance;

[0152] (2) From the comparison between Examples 1, 4, 5 and Examples 18 and 19, it can be seen that if the concentration of the added acid solution is too low, the sharp corners cannot be effectively removed, and if the acid solution is too high in concentration, the acidification range will be increased. In the ball milling process, not only the sharp corners are removed, but also the irregular particles are deformed, and some particles are deformed into flaky shapes, which reduces the performance. Only when the concentration of the acid solution is controlled within a certain range can the sharp corners be effectively acidified, and only by removing them through ball milling can particles close to spherical shapes be produced, thereby improving the performance of Sendust.

[0153] (3) From the comparison between Examples 1, 6, 7 and Examples 20, 21 and Comparative Example 1, it can be seen that when the amount of acid solution added is small or even no acid solution is added, the crushed iron-silicon-aluminum cannot be completely submerged, and the entire crushed iron-silicon-aluminum cannot be completely acidified. Although the performance is improved, it cannot reach the best; when an excessive amount of acid solution is added, not only the sharp corners of the crushed iron-silicon-aluminum are acidified, but also the entire irregular crushed iron-silicon-aluminum particles are acidified, and part of the crushed iron-silicon-aluminum particles are turned into flakes during ball milling, and the performance is seriously degraded;

[0154] (4) From the comparison between Examples 1, 8, 9 and Examples 22 and 23, it can be seen that when the amount of grinding balls added is small, the sharp corners of acidification cannot be completely removed; and when the amount of grinding balls added is large, the energy generated is large, and flaky sendust is also generated, and the performance is poor;

[0155] (5) From the comparison between Examples 1, 10, 11 and Examples 24 and 25, it can be seen that when the ball milling time is too short, only a small amount of acidified sharp corners can be removed, and most of the sharp corners have not yet been removed, and the performance can only be slightly improved; and when the ball milling time is too long, in addition to removing the sharp corners, the particle shape will also be deformed, and more irregular shaped particles, including flakes, will appear, and the performance will be reduced. Therefore, the ball milling time can only be within a certain range to completely remove the sharp corners and make the irregular particles deform into a state close to spherical particles, so as to obtain higher performance and meet production needs;

[0156] (6) From the comparison between Examples 1, 12, 13 and Examples 26 and 27, it can be seen that when the ball milling speed is low, only a small amount of acidified sharp corners can be removed, and most of the sharp corners have not yet been removed, and the performance can only be slightly improved; while when the ball milling speed is high, in addition to removing the sharp corners, the particle shape will also be deformed, and more irregular shaped particles, including flakes, will appear, and the performance will be reduced. The ball milling speed can only be within a certain range to completely remove the sharp corners and make the irregular particles deform into a state close to spherical particles, so as to obtain higher performance and meet production needs;

[0157] (7) From the comparison between Examples 1, 14, 15 and Examples 28 and 29, it can be seen that the terminal temperature of the heating in step (2) of the present invention, that is, the insulation temperature, will affect the performance of the obtained Sendust aluminum. When the insulation temperature is low, the median particle size of Sendust aluminum will increase, the density will decrease, the magnetic loss at 100kHz / 100mT will increase, and the 100Oe DC bias performance will decrease. This is because when the insulation temperature is low, the internal stress cannot be completely eliminated, the grain boundary moves, resulting in grain growth, increased porosity, and only a small number of grains form new destinations. When the insulation temperature is high, the median particle size of Sendust aluminum will increase, the density will decrease, the magnetic loss at 100kHz / 100mT will increase, and the 100Oe DC bias performance will decrease. This is because the grains grow abnormally, the porosity increases, resulting in lattice deformation and dislocation, affecting the magnetic properties of Sendust aluminum.

[0158] (8) From the comparison between Example 1 and Examples 30 and 31, it can be seen that the mass ratio of the glue described in step (3) of the present invention to the sendust powder obtained in step (2) will affect the performance of the sendust; when the mass ratio is low, the median particle size of the sendust becomes larger, the density becomes smaller, the magnetic loss at 100kHz / 100mT becomes larger, and the 100Oe DC bias performance becomes smaller. This is because the glue cannot completely cover the powder, and powder loss and layer cracking will occur during pressing, resulting in unstable performance; when the mass ratio is high, the median particle size of the sendust becomes larger, the density becomes smaller, the magnetic loss at 100kHz / 100mT becomes larger, and the 100Oe DC bias performance becomes smaller. This is because when there is too much glue, it will stick to the mold, reducing the magnetic properties;

[0159] (9) From the comparison between Example 1 and Comparative Example 2, it can be seen that the preliminary heat treatment of the ball-milled material obtained in step (1) in step (2) of the present invention will affect the performance of the obtained Sendust; when the preliminary heat treatment of the ball-milled material obtained in step (1) in step (2) is omitted, the median particle size of Sendust becomes larger, the density becomes smaller, the magnetic loss at 100kHz / 100mT becomes larger, and the 100Oe DC bias performance becomes smaller. This is because the main function of the preliminary annealing is to eliminate internal stress, refine grains, adjust grain orientation, reduce porosity, improve magnetic properties, etc.

[0160] (10) From the comparison between Example 1 and Comparative Example 3, it can be seen that the method for improving the crushing performance of sendust provided by the present invention can prepare sendust with low loss and high DC bias performance, and the loss of the prepared sendust at 100kHz / 100mT is not higher than 550mW / cm 3 , the DC bias performance under a magnetic field strength of 100Oe is not less than 27%; at the same time, the method also has the advantages of low cost, simple process and easy large-scale promotion and use.

[0161] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for improving the performance of crushing iron, silicon and aluminum, characterized in that: The method comprises: The crushed sendust is ball-milled, an acid solution is added during the ball-milling process, and then a first annealing is performed in a protective atmosphere to obtain sendust powder, the obtained sendust powder is mixed with glue and then pressed, and then a second annealing is performed in a protective atmosphere to obtain sendust.

2. The method according to claim 1, characterized in that The ball mill uses first grinding balls and second grinding balls with different diameters; Preferably, the size of the first grinding ball is 2-4 mm, and the size of the second grinding ball is 4-6 mm; Preferably, the mass ratio of the first grinding ball to the second grinding ball is (2-4):1; Preferably, the mass ratio of all grinding balls in the ball mill to the mass ratio of the crushed iron-silicon-aluminum is (4-8):1; Preferably, the ball milling time is 8 to 12 hours; Preferably, the rotation speed of the ball mill is 50-100 r / min.

3. The method according to claim 1 or 2, characterized in that: During the ball milling process, the mass ratio of the crushed iron-silicon-aluminum to the added acid solution is 1:(1-2); Preferably, the acid solution comprises any one of a nitric acid solution, a sulfuric acid solution or a hydrochloric acid solution or a combination of at least two thereof, preferably a nitric acid solution; Preferably, the volume concentration of the acid solution is 0.5-1.5%.

4. The method according to any one of claims 1 to 3, characterized in that: The process between the ball milling and the first annealing includes washing, drying and screening in sequence; Preferably, the cleaning solution used for cleaning includes ethanol.

5. The method according to any one of claims 1 to 4, characterized in that: The first annealing includes a first heating and a first heat preservation performed sequentially; Preferably, the first heating rate is 2-3°C / min, and the end temperature is 620-630°C; Preferably, the first insulation time is 60 to 120 minutes.

6. The method according to any one of claims 1 to 5, characterized in that: The mixing comprises: firstly mixing the coupling agent solution with the obtained sendust powder, stirring until the solvent of the coupling agent solution is completely volatilized to obtain a first mixed material; secondly mixing glue with a glue solvent to obtain a glue solution; thirdly mixing the obtained first mixed material with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized; Preferably, the mass ratio of the coupling agent to the sendust powder in the coupling agent solution is (1-3):100; Preferably, the concentration of the coupling agent in the coupling agent solution is 95-99.9%; Preferably, the solvent of the coupling agent solution includes ethanol and / or acetone; Preferably, the mass ratio of the glue to the sendust powder obtained in step (2) is (1-3): 100; Preferably, the glue solvent comprises acetone and / or ethanol.

7. The method according to any one of claims 1 to 6, characterized in that: The pressing comprises a ring pressing process to obtain a ring embryo body; Preferably, the pressure of the ring pressing treatment is 1800-2000 MPa.

8. The method according to any one of claims 1 to 7, characterized in that: The second annealing includes a second heating and a second heat preservation performed sequentially; Preferably, the second heating rate is 2-4°C / min, and the end temperature is 650-750°C; Preferably, the second insulation time is 30 to 90 minutes.

9. The method according to any one of claims 1 to 8, characterized in that: The method comprises: (1) ball milling the crushed iron-silicon-aluminum at a speed of 50 to 100 r / min for 8 to 12 hours, and then washing, drying and sieving in sequence to obtain a ball-milled material; The ball mill uses a first grinding ball with a diameter of 2 to 4 mm and a second grinding ball with a diameter of 4 to 6 mm, the mass ratio of the first grinding ball to the second grinding ball is (2 to 4):1, and the mass ratio of all the grinding balls to the crushed iron-silicon-aluminum is (4 to 8):1; during the ball milling process, an acid solution with a volume concentration of 0.5 to 1.5% is added, and the mass ratio of the crushed iron-silicon-aluminum to the added acid solution is 1:(1 to 2); (2) heating the ball-milled material obtained in step (1) to 620-630° C. at a rate of 2-3° C. / min in a protective atmosphere and then keeping the temperature for 60-120 min to obtain sendust powder; (3) first mixing the coupling agent solution with the sendust powder obtained in step (2), stirring until the solvent of the coupling agent solution is completely volatilized, to obtain a first mixed material; second mixing glue with the glue solvent to obtain a glue solution; third mixing the first mixed material with the obtained glue solution and stirring until the glue solvent in the glue solution is completely volatilized, and then performing a ring pressing treatment at a pressure of 1800 to 2000 MPa to obtain a ring embryo; The concentration of the coupling agent in the coupling agent solution is 95-99.9%, and the mass ratio of the coupling agent in the coupling agent solution to the sendust powder obtained in step (2) is (1-3):100; the mass ratio of the glue to the sendust powder obtained in step (2) is (1-3):100; (4) The ring body obtained in step (3) is heated to 650-750° C. at a rate of 2-4° C. / min in a protective atmosphere and then kept at this temperature for 30-90 min to obtain Sendust.

10. Sendust, characterized in that: The Sendust is obtained by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing composite powder core with magnetic conductivity equal to 60 and used for high-power electric reactors

    CN107610872A

  • Preparation method of high-DC biasing and high-frequency stability Fe-Si-Al powder core

    CN107919202A